Wahbah Az-Zuhaili’s thoughts on social education in surah Al-Hujurat verses 10-13: A study on Al-Munir’s interpretation - Taubatan Nasuha (Nalar Global Foundation, 2020)
This study aims to determine Wahbah Az-Zuhaili's thoughts on social education in surah Al-Hujurat verses 10-13 by studying Al-Munir's interpretation and identifying what methods that can be used to design instructional activities for teaching social education based on the contents of surah Al-Hujurat verses 10-13. This study was carried out in the design of library research, which used various literatures as the sources of research data and maudu'i as the interpretation method. Primary data sources are the Qur'an and At-Tafsir al-Munir fil-Aqidah wasy-Syari'ah wal-Manhaj. Then, secondary data sources include books, articles, magazines, newspapers, and other sources which are relevant to the primary data. Based on the results of analysis, it can be concluded that surah Al-Hujurat verses 10-13 discusses in detail about attitudes and social education.